Platelet microvesicles in health and disease. (3rd April 2017) - Melki, Imene; Tessandier, Nicolas; Zufferey, Anne; Boilard, Eric
Abstract: Interest in cell-derived extracellular vesicles and their physiological and pathological implications is constantly growing. Microvesicles, also known as microparticles, are small extracellular vesicles released by cells in response to activation or apoptosis. Among the different microvesicles present in the blood of healthy individuals, platelet-derived microvesicles (PMVs) are the most abundant. Their characterization has revealed a heterogeneous cargo that includes a set of adhesion molecules. Similarly to platelets, PMVs are also involved in thrombosis through support of the coagulation cascade. The levels of circulatory PMVs are altered during several disease manifestations such as coagulation disorders, rheumatoid arthritis, systemic lupus erythematosus, cancers, cardiovascular diseases, and infections, pointing to their potential contribution to disease and their development as a biomarker. This review highlights recent findings in the field of PMV research and addresses their contribution to both healthy and diseased states.